2022
DOI: 10.3389/fsoc.2022.832201
|View full text |Cite
|
Sign up to set email alerts
|

The Lost Social Context of Recovery Psychiatrization of a Social Process

Abstract: From being a concept questioning the core of psychiatric knowledge and practice, recovery has been adopted as a guiding vison for mental health policy and practice by different local, national, and international organizations. The aim of this article is to contextualize the different understandings of recovery and its psychiatrization through the emergence of an individualizing and de-contextualized definition which have gained a dominant position. It ends with an attempt to formulate a new definition of recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 111 publications
(156 reference statements)
0
24
0
2
Order By: Relevance
“…It might be a prison or a working place in the woods. Recovery is about collecting the good stories about places and people that include the psycho-socio-material contexts ( Topor et al, 2020 ) and at the same time remembering how bad it once was.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be a prison or a working place in the woods. Recovery is about collecting the good stories about places and people that include the psycho-socio-material contexts ( Topor et al, 2020 ) and at the same time remembering how bad it once was.…”
Section: Discussionmentioning
confidence: 99%
“…He describes how people having mental health problems suffer from ‘material deprivation’ because they often live in poor neighbourhoods and poor housing conditions, resulting in social exclusion and non-recovery (Boardman, 2011). To specifically include the social and material perspective, Topor et al (2020) suggested a social model to understand recovery: Recovery is a deeply social, unique and shared process in which our living conditions, material surroundings, attitudes, values, feelings, skills, and/or roles are changing.It is a way of living satisfying, hopeful, and contributing lives, together with others even though we may still experience distress, unusual experiences and troubled or troubling behaviour. 1 Recovery involves engaging in new material and social contexts and in open dialogues where new understandings of the situation we find ourselves in are created as we move beyond a psycho-social-material crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Personens hverdagsliv og lokalmiljø, fellesskap, samspill og samarbeid med andre og levekår vies stor oppmerksomhet. Det handler om å ta kontrollen tilbake, finne mening og leve det livet personen ønsker og kan Topor, Bøe & Larsen, 2022).…”
Section: Recovery -Fra Kollektivt Opprør Til Faglig Standardisering?unclassified
“…The initial meaning of recovery integrates persons in their social context but has over the years been diluted and taken a more individualistic form. In recent years explanation of recovery as only a personal journey has re-evolved to include the person´s social context were social aspects as relationships and living conditions are considered as important for recovery (Topor et al, 2011 , 2022 ). In a modern recovery-oriented practice, it is important as a health care professional to have a holistic approach.…”
Section: Introductionmentioning
confidence: 99%